Karl Marx is a Thinker and Creator of the Future - Chereshnev, Valeriy Aleksandrovich; Ivanitsky, Viktor Pavlovich (Economy of Regions, 2018)
The article considers Karl Marx, an outstanding thinker, who thanks to his knowledge of philosophy, history, and economics has managed to predict the stages and forms for economic, social and, substantially, spiritual development of peoples. His vision of the future is based on the thoughtful, real, and significant understanding of the economic activity of human society. Generally, the scientific community with rather deep and sincere respect paid attention to his ability to expect the future for centuries forward. This article is not just a tribute to the 200 anniversary since the birth of the genius. Now in the 21st century, K. Marx's anniversary is, first of all, the recognition of his genius. Living now, we see the economic, social and spiritual development of humanity in the conditions of convergence of science, education, quality of life, human health, warm-heartedness and credibility in overcoming even small challenges. We strive for a careful attitude to nature, rational use of its gifts and natural wealth. Only in such harmony, the mankind will have a happy future.